INFLUENCE OF SALVAGE VALUE UPON CHOICE OF TAX DEPRECIATION METHODS. - Myers, John H. (The Accounting Review, 1960)
Abstract This article focuses on the influence of salvage value upon choice of tax depreciation methods. It is found that on should use double-declining balance depreciation method for tax purposes whenever salvage value exceeds 13.52 percent of cost. For such a rule to stand there must be an examination of the underlying assumptions, law, and mathematics. The fundamental assumption underlying preference for this method of depreciation is that the taxpayer would rather have a tax deduction now than later. The assumption of preference for a present rather than a future tax deduction is based on assumptions. Pre-depreciation income in the current and near-future years is large enough to yield a tax benefit from the largest allowable depreciation deduction. It does not seem sensible to plan to reduce basis and to incur a tax loss in order to get net operating loss carry-oven. There may be certain cases where such is desirable, but a tax deduction is certain whereas one in the future is not certain. Although a deduction for depreciation has been allowed since the inception of income tax laws, there is no certainty that it will continue in the present form.